Microfluidic Methods for Production of Liposomes - Yu, Bo (2009)
Liposomes are composed of lipid bilayer membranes that encapsulate an aqueous volume. A major challenge in the development of liposomes for drug delivery is the control of size and size distribution. In conventional methods, lipids are spontaneously assembled into heterogeneous bilayers in a bulk phase. Additional processing by extrusion or sonication is required to obtain liposomes with small size and a narrow size distribution. Microfluidics is an emerging technology for liposome synthesis, because it enables precise control of the lipid hydration process. Here, we describe a number of microfluidic methods that have been reported to produce micro/nanosized liposomes with narrower size distribution in a reproducible manner, focusing on the use of continuous-flow microfluidics. The advantages of liposome formation using the microfluidic approach over traditional bulk-mixing approaches are discussed.